Thrombocytopenia Rates In Newborns Diagnosed With Gram-Negative Sepsis. Insights From NICU Experimental Based Study - Shahalam, Sobia; Iqbal, Madiha; Hassan, Sara; Rizwan, Shazia; Waseem, Rizwan; Rehman, Rabeya (Journal of Rawalpindi Medical College, 2025)
Objective: To evaluate the prevalence of thrombocytopenia observed in neonates admitted to the hospital with sepsis. Methods: A total of 103 patients, including both males and females with ages below 28 days, who were admitted to the NICU (neonatal intensive care unit) with gram-negative sepsis were enrolled in this study. Blood samples were collected from each patient for sepsis and platelet analysis on the 1st and 3rd day of patients’ admission and sent to the Ghurki Hospital laboratory for analysis. Thrombocytopenia was defined as platelet counts <150,000/mm3. Thrombocytopenia was classified as mild, moderate, and severe. The type of organism and mortality rate related to thrombocytopenia were also recorded. Results: Of 103 neonates, 64 (62.13%) were males while 39 (37.86%) were females. 88 (85.43%) had thrombocytopenia (p <0.001) whereas 15 (14.56%) had normal platelet count. E. coli was found to be the most common organism responsible for gram-negative sepsis. On day one, 61 (59.22%) patients had normal platelet count whereas 12 (11.65%), 14 (13.59%), & 16 (15.53%) neonates had mild, moderate & severe thrombocytopenia respectively. In contrast, on the third day, 18 (17.47%) neonates had normal platelet count, 6 (5.82%) had mild, 33 (32.03%) had moderate, and 46 (44.66%) had severe thrombocytopenia. 12/103 (11.65%) patients died, out of which 11 (10.68%) had thrombocytopenia. Conclusion: Thrombocytopenia is a significant marker of gram-negative sepsis in neonates. Keywords: Neonate, Neonatal Intensive Care Unit, Thrombocytopenia, Sepsis.